Comments on 'Lattice Boltzmann simulation of alumina-water nanofluid in a square cavity' - Che Sidik, Nor Azwadi (2012)
This work presents some comments concerning the paper entitled ‘Lattice Boltzmann simulation of alumina-water nanofluid in a square cavity’ by Yurong He, Cong Qi, Yanwei Hu, Bin Qin, Fengchen Li and Yulong Ding which was published in Nanoscale Research Letters in 2011. The comments are related to the numerical parameters and the computed results of average Nusselt number.